Avaliação qualiquantitativa da sustentabilidade urbana em HIS pelo Selo Casa Azul e Sbtool Urban - Gonçalves, Djanny Klismara de Oliveira (Universidade Federal de São Carlos, 2020)
The unsustainable profile Brazilian social housing (SH) has expressed major impacts on the population's quality of life, on the natural environment and on the systems that make up cities. In this sense, the assessment of the sustainability potential of these housing developments is necessary as a way of identifying the main weaknesses of the assessment systems, contributing to the process of improving the assessment tools, especially in relation to the productive processes and insertion in the urban mesh. Based on the post-occupation analysis of a SH project implemented in the city of Araraquara, São Paulo state, the objective was to develop an evaluation on urban sustainability in order to improve the Casa Azul Seal, with the aim of based on a multi-method approach based on the SBTool Urban certification tool. It was proposed to apply the calculations established in SBTool Urban according to the requirements of the Casa Azul Seal, together with the insertion of a national benchmark to establish the analysis. In this way, four categories of the Casa Azul Seal were analyzed according to the survey of the case study information carried out by document analysis, technical visits and analysis of the guidelines required by the public administration. As a result, it was possible to attest to the unsustainability profile of the enterprise with the low values verified by the calculations, as well as to understand the advantages and limitations of the referential analysis. As an advantage, the adoption of the benchmark allowed a foundation for the improvement framework, as well as the possibility of frequent renewal of the assessment as new requirements are established that configure greater sustainability to the enterprise. On the other hand, it was identified the need for scientific investigation of social housing projects that present a potential for greater sustainability so that referenced assessments can be carried out with technical basis.
Qualitative and quantitative assessment of urban sustainability in social housing using the Casa Azul Seal and SBTool Urban
Keywords: Selo casa azul; Certificações ambientais; Habitação de interesse social; Casa azul seal; Environmental certifications; Social housing; SBTool urban; ENGENHARIAS